Climatic trends, risk perceptions and coping strategies of smallholder farmers in rural Uganda - Mubiru, DN; Kyazze, Florence Birungi; Radeny, Maren A.O.; Zziwa, A.; Lwasa, J.; Kinyangi, James (2015)
Smallholder farmers in Uganda face a wide range of agricultural production risks, with climate change and variability presenting new risks and vulnerabilities. Climate related risks such as prolonged dry seasons have become more frequent and intense with negative impacts on agricultural livelihoods and food security. This paper assesses farmers’ perceptions of climate change and variability and analyses historical trends in temperature and rainfall in two rural districts of Uganda in order to determine the major climate-related risks affecting crop and livestock production and to identify existing innovative strategies for coping with and adapting to climate-related risks, with potential for up-scaling in rural districts. The traditional coping strategies that have been developed by these communities overtime provide a foundation for designing effective adaptation strategies.